Benign and malignant skin lesions in renal transplant recipients - Ghaninejad H; Ehsani A; Ghiasi M; Noormohammadpour P; Najafi E; Naderi G; Ganji M; Mirnezami M; Nezami R; Kiani P (Wolters Kluwer Medknow Publications, 2009)
Background: Skin lesions - benign and malignant - occur frequently in organ transplant recipients receiving long-term immunosuppressive therapy. These patients are at greater risk of skin cancers. Aims: To study dermatologic problems in renal transplant recipients (RTRs). Methods: One hundred patients (53 men and 47 women) were consecutively examined for benign and malignant skin complications since transplantation in Razi Hospital in Tehran Medical University. The main immunosuppressive therapy regimen in these patients was a combination of prednisolone, azathioprine, and cyclosporine. Results: The early and most common complication was cosmetic side effects that occurred in 98% patients. Skin infections occurred in 83% of the patients and most of them were viral infections (65%), especially of human papilloma viruses (HPVs) in 40% of the patients. We found six cases of malignancy in these patients in that four cases were skin cancers, including one case of SCC, one BCC, and two cases of Kaposi′s sarcoma. Dermatologic problems occur most frequently in RTRs, especially skin cancers which have higher frequency in these patients than general population, particularly, Kaposi sarcoma. Sun exposure has an important role in developing epithelial skin cancers following transplantation. The age of developing skin cancer in these patients was early than normal population. Conclusion: Our results emphasize the importance of dermatologic examinations and monitoring RTRs to obtain an early diagnosis and treatment of cutaneous manifestations.